Heparin binding analysis of boar sperm and its relation with farrowing capacity - Dapino, Dora Gabriela (2014)
New methods for the evaluation of semen quality according to in vivo reproductive data are useful tools for identifying boars of lower fertility among individuals with standard semen parameters. In this study, indirect fluorescence microscopy was used to evaluate the heparin binding site distribution upon capacitation of sperm from eight boars arbitrarily distributed into Groups I and II according to differential farrowing rates (Group I: ≥ 70%, Group II: < 70%). Additionally, the ability of sperm to bind to solubilised zona pellucida (ZP) was assayed in the presence or absence of heparin. Samples of two individuals of Group II showed lower percentage of B pattern in relation to other individuals (P < 0.001). The number of spermatozoa attached to ZP after 2 h of incubation in capacitating conditions with heparin was significantly lower than in its absence (P < 0.0001). These results suggest that heparin binding site distribution concerning capacitation may be indicative of the availability of proteins involved in the fertilisation process, specifically at the initial sperm-oocyte recognition. Differences in heparin binding site dynamics during capacitation may help identify a subpopulation of individuals with lower fertilising capacity and normal spermiogram, which is particularly useful at high-production establishments.